Factors influencing the addiction characteristics of non-suicidal self-injurious behaviors in adolescents: A case-control study - Zhu, Junhong; Qian, Rui; Zhong, Hao; Li, Yi; Liu, Xuebing; Ma, Jun (Frontiers in Psychiatry, 2022)
Background Many studies have shown that in the context of public health emergencies, the incidence rate of adolescent non-suicidal self-injury (NSSI) patients increased dramatically. This paper aims to characterize the behavioral characteristics of adolescent NSSI and analyze the influencing factors of NSSI behavior addiction characteristics. Methods Our research was a case-control study which included 84 adolescents with NSSI (female vs. male: 59 vs. 25) and 84 healthy controls (female vs. male: 53 vs. 31). All the participants enrolled were aged 12-18 years. The differences in the scores of the following five scales were compared between the case and control groups: Egna Minnen Barndoms Uppfostran (EMBU), Perceived Social Support Scale (PSSS), Perceived Stress Scale (PSS); Bergen Social Media Addiction Scale (BSMAS) and Video Game Dependence Scale (VDG-S). The characteristics of NSSI behavior of the study group were evaluated using the Ottawa Self Inventory Chinese Revised Edition (OSIC). And a binary logistic regression model was developed to analyze the factors that influence adolescent NSSI behavioral addiction characteristics. Results In the study group, the emotional warmth scores in the father’s and mother’s rearing style scores in the EMBU were significantly lower than the controls. The BSMAS and VDG-S scores were significantly higher than those in the control group. 38 cases of NSSI with addiction characteristics accounted for 45.24% in the study group. The risk factors for NSSI addiction traits were as follows: female, single-child, high level of VDG-S scores, high scores of excessive interferences in father’s rearing style, and high scores of punishments and excessive interferences in mother’s rearing style score. Conclusion Female, only child, internet addiction, and negative parenting styles were predictors of NSSI behavioral addiction characteristics in adolescents. Targeted coping strategies should be developed to reduce the occurrence and development of self-injurious behavior, especially for female adolescents with Internet dependence in one-child families with negative parenting styles.